Effect of Normal Saline versus PlasmaLyte on Coagulation and Metabolic Status in Patients Undergoing Neurosurgical Procedures - Arora, Vandna; Khatri, Akanksha; Bala, Renu; Kumar, Vibhuti; Arora, Rashmi; Jindal, Shweta (Asian Journal of Neurosurgery, 2023)
Background The choice of intraoperative fluid in neurosurgical patients is important as we need to maintain adequate cerebral perfusion and oxygenation and also avoid cerebral edema. Normal saline (NS) is commonly used in neurosurgeries, but it leads to hyperchloremic metabolic acidosis, which may result in coagulopathy. Balanced crystalloid with physiochemical composition akin to that of plasma has favorable effects on metabolic profile and may avoid the problems associated with NS. Against this background, the present study aimed to compare the effects of NS versus PlasmaLyte (PL) on coagulation profile in patients undergoing neurosurgical procedures.Methods This prospective, randomized, double-blinded study was conducted in 100 adult patients scheduled to undergo various neurosurgical procedures. Patients were randomly allocated in two groups of 50 each to receive either NS or PL intraoperatively and postoperatively till 4 hours after the surgery. Hemoglobin, hematocrit, coagulation profile (PT, PTT, and INR), serum chloride, pH, blood urea, and serum creatinine were measured prior to induction (baseline) and 4 hours after completion of surgery.Results Demographic characteristics were statistically similar between the two groups. Coagulation profile parameters were comparable between the two groups at baseline as well as 4 hours after surgery. pH was significantly lower in the NS group as compared to the PL group at 4 hours after surgery. Postoperatively blood urea, serum creatinine, and serum chloride levels were significantly raised in the NS group as compared to the PL group. Hemoglobin and hematocrit values were similar between the two groups.Conclusion Coagulation profile parameters were normal and statistically similar with intraoperative infusion of NS versus PL in patients undergoing neurosurgical procedures. However, use of PL was associated with a better acid–base and renal profile in these patients.
Keywords: coagulopathy; crystalloid; PlasmaLyte; normal saline; neurosurgery